Mesurer la ville par l’évaluation et la caractérisation du sol urbain : l’exemple de Tours - Amélie Laurent; Mélanie Fondrillon (Revue Archéologique du Centre de la France)
Two recent archaeological theses have been involved with the understanding of the urban archaeology of Tours and conducted as part of the archaeological research developed over a 40-year period. They particularly cover the analysis of the characteristics and principles of the raising of urban land, corresponding to the entire archaeological deposits of a city.These works concerned two complementary scales traditionally employed in urban archaeology: evaluation, on the scale of the city, and characterisation, on the scale of the site. Based on the use of tools from earth science and applied to a problematic city history, two new approaches to pre-industrial city stratigraphy have been developed, the first concerning micro-archaeology, the second, geotechnics applied to the archaeological deposits.Conducted jointly, these two studies are doubly interesting: first, of a general nature, concerning the implementation of a methodology applicable to all urban phenomena, in particular by the creation of a common frame of reference for archaeological stratum, enabling undefined deposits to be described; the second interest, more selective, concerns the application of these general principles to one particular case of urban land formation, that of Tours. The modelling of results to the scale of the city implies that the acquisition of data on the ground incorporates a problematic history and topography.